Citation Characteristics of Mathematical Literature - Мальцене, Лилиана (Knygotyra, 1985)
Data on distribution of bibliographic references contained in the publication on mathematics are given: as distributed by type, language and year of publication of the paper cited. The data on self-citations were also investigated, and the self-citation rate as compared with the total of references in the given article has been found and defined.